Military Responses to the Arab Uprisings and the Future of Civil-Military Relations in the Middle East : Analysis from Egypt, Tunisia, Libya, and Syria - Taylor, William C. (New York Palgrave Macmillan, 2014)
This book explains Arab military responses to the social uprisings which began in 2011. Through a comparative case study analysis of Egyptian, Tunisian, Libyan, and Syrian militaries, it explains why militaries fractured, supported the regime in power, or removed their presidents.
Include Bibliography and Index
Keywords: Tunisia -- Libya -- Egypt